Responses to Recurrent Index Selection for Reduced Fusarium Ear Rot and Lodging and for Increased Yield in Maize. Issue 1 (1st January 2016) - Horne, David W.; Eller, Magen S.; Holland, James B.
ABSTRACT: Fusarium ear rot, caused by the pathogen Fusarium verticillioides, damages maize ( Zea mays L.) grain production and is associated with contamination of grain by fumonisin, a mycotoxin harmful to both humans and animals. Recurrent selection may be an effective way to combine improvements in resistance to Fusarium ear rot with improved grain yield and lodging resistance. To test this hypothesis, three cycles of recurrent index selection based on evaluating S0:1 lines for Fusarium ear rot, grain yield, and lodging were implemented in a genetically broad‐based population. Direct intrapopulation response to selection in the target traits was measured by comparing lines sampled from Cycle 0 and Cycle 3 populations. In addition, indirect response for fumonisin contamination was also measured along with indirect response for agronomic traits when crossed to commercial inbred tester, FR1064. Results indicate significant direct gain from selection for Fusarium ear rot, but no significant gains for yield or lodging resistance. Indirect gains were also observed for Fusarium ear rot resistance in topcrosses to an unrelated tester line and for fumonisin contamination both within the selection population and in topcrosses. Our results are the first demonstration of the indirect effect of selection against Fusarium ear rot on reduction of fumonisin contamination. Heritabilities for target traits did not decrease over generations, indicating potential for further genetic gain from selection in this population.